PROGRAM IMITAN INDUSTRI SEBAGAI UPAYA MENINGKATKAN SERAPAN LULUSAN YANG BEKERJA DI DUNIA INDUSTRI DI SMK NEGERI 2 PENGASIH - Fajrina Sulistyani; Agustina Sri Purnami; Sunarto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Vocational High School graduates are the biggest contributor to the unemployment rate in Indonesia, therefore steps and actions are needed to overcome this. Industrial imitation is a program to increase the uptake of graduates in the industrial world. This program is an activity carried out at SMK N 2 Kasih, Kulon Progo. The aims of this study were to find out: (1) the management of the Imitan Industri program in an effort to increase graduate uptake in SMKs; (2) supporting factors for the Industrial Imitation program; (3) inhibiting factors for the Industrial Imitation program; (4) activity program in Industrial Imitation. The type of research used is descriptive qualitative. Interviews, observations, and documentation studies are ways of collecting techniques. Data reduction, data presentation, drawing conclusions and preparing recommendations are used in data analysis techniques. The results showed: (1) the management of the Industrial Imitation program at SMK N 2 Pengasih; (2) supporting factors in the form of adequate financial availability, planned and measurable programs, students who are enthusiastic about participating in the industrial imitation program, parents of students who support the industrial imitan program, professional educators; (3) the inhibiting factor in the form of limited time availability can be overcome by using hours outside of the KBM (Learning and Teaching Activities. There are not many companies that work together; (4) some of the activities in the Industrial Imitation program include physical training, psychological test training, training character, and material provision by alumni of the Industrial Imitation program.